The Influences of Job Satisfaction and Performance on Employees Followership Styles: A Survey in the Malaysian Health Institution - ., Saraih; Naiemaha, Ummi; ., Razali; ., Razleenab; Abduljabbar, Abdulsatar; ., Sultanc; ., Rozali; Farah Aliaad, Nor (International Journal of Engineering and Technology, 2018)
The present study examined the influences of job satisfaction and job performance on followership style among employees from one of the public health institution in the Northern Malaysia. This study utilized the questionnaire method. A total of 210 respondents including the administrative staff, medical officer and nurses participated in this study. The findings presented that employees in this institution have moderately high levels of followership style (mean=3.67), job satisfaction (mean=3.67) and job performance (mean=3.37). Results presented that job satisfaction is significantly related to followership style (Î²=.72, p=.00); and job performance is not significantly related to followership style (Î²=-.11, p=.12). Thus, it is found that only job satisfaction has a significant influence on followership style among employees in this institution. This study contributed some fruitful knowledge which can be suggested to all of the Malaysian public health institution, particularly to improve the level of followership style. Implications of the results are discussed; and limitations of this study are briefly highlighted.Â